Cataract surgery and DMEK: decision-making and the timing of the respective interventions = Katarakt-Operation und DMEK: welche OP zu welchem Zeitpunkt? - Augustin, Victor A.; Friedrich, Maximilian; Son, Hyeck Soo; Yildirim, Timur Mert; Auffarth, Gerd U.; Khoramnia, Ramin (Klinische Monatsblätter für Augenheilkunde, 2025)
With the introduction of Descemet membrane endothelial keratoplasty (DMEK), the treatment of endothelial corneal diseases such as Fuchsʼ corneal endothelial dystrophy (FECD) has been significantly optimised. Thanks to rapid and good visual rehabilitation, surgery is advised in earlier stages of the disease. When patients are 50 - 70 years old, not only the FECD, but also cataract can become increasingly functionally relevant. It is therefore important to accurately assess and quantify the functional limitations of both conditions, in order to determine which surgery (DMEK and/or cataract surgery) is more useful and imminent. One possibility is to perform a so-called triple DMEK (DMEK combined with cataract surgery). This is an option for phakic patients who are no longer able to accommodate and have clinical or subclinical, tomographic corneal oedema, as this would avoid early DMEK subsequent to cataract surgery. However, if cataract patients with FECD do not exhibit any relevant (clinical or subclinical) corneal oedema, they may benefit from cataract surgery alone without DMEK. Nevertheless, visual quality may remain limited by the corneal guttae and DMEK may still be necessary later. The third option is to perform DMEK without cataract surgery in phakic patients. This may be considered in young FECD patients without cataract who are still accommodating FECD. However, it is important to note that when cataract surgery is required later, the endothelial cell loss resulting from cataract surgery may lead to earlier DMEK graft failure. Overall, in patients with FECD and an age-related lens opacification or incipient cataract, the need and timing of the respective intervention must be determined individually, in order to achieve the optimal therapeutic success. The procedure described in this manuscript can help support decision-making and the timing of the respective interventions.
Artikel in mehreren Sprachen: Englisch und Deutsch
Gesehen am 21.01.2026